BANKING CREDIT IN BRAZIL: A PANEL DATA ANALYSIS OF LARGER INSTITUTIONS - Fucidji, José Ricardo (2010)
This paper brings some new evidence on the banking behavior concerning credit, using bank-level data of the thirteen largest banks located in Brazil (domestic and foreign). After a brief overview of the literature on the Brazilian banking sector restructuring (following the Real Plan) and lending behavior, we implement a panel data analysis on our sample, from March 2001 to June 2006. The main results are: (1) a robust negative correlation between public bonds purchase and lending; and (2) a robust positive correlation between demand deposits, leverage and GDP at constant prices, on the one hand; and lending, on the other hand. These findings, particularly leverage and public bonds purchase, seem to confirm high liquidity-preference of the banking sector. Brazilian prime rate (Selic) and Basle index, also included, were of no-significance.